Coumarins from Malaysian Micromelum minutum - Rahmani, Mawardi; Susidarti, Ratna Asmah; Mohd Ismail, Hazar Bebe; Md. Sukari, Mohd Aspollah; Yap, Taufiq Yun Hin; Ee, Gwendoline Cheng Lian; Ali, Abdul Manaf; Kulip, Julius; Waterman, Peter G. (Elsevier, 2003)
In a continuation of our study of the Rutaceae, detailed chemical investigation on Micromelum minutum (Rutaceae) collected from Sepilok, Sabah, Malaysia gave four new coumarins. The structures of the coumarins have been fully characterised by spectroscopic methods as 3″,4″-dihydrocapnolactone 1, 2′,3′-epoxyisocapnolactone 2, 8-hydroxyisocapnolactone-2′,3′-diol 3 and 8-hydroxy-3″,4″-dihydrocapnolactone-2′,3′-diol 4.